Identification and functional characterization of the sulfakinin and sulfakinin receptor in the Chinese white pine beetle Dendroctonus armandi - Liu, Bin; Fu, Danyang; Ning, Hang; Tang, Ming; Chen, Hui (Frontiers in Physiology, 2022)
The Sulfakinin (SK) is an important signaling molecule that acts as a neuromodulator to mediate a diversity of physiological functions and behavioral processes in the invertebrates, by the interaction with SK receptors, which are a kind of G protein-coupled receptor (GPCR). However, there are no reports on the functional roles of SK in Chinese white pine beetle, Dendroctonus armandi Tsai & Li, (Coleoptera: Curculionidae, Scolytinae). We have cloned and characterized SK and SKR genes in the D. armandi and made bioinformatics predictions according to the deduced amino acid sequences. They were highly similar to that of Dendroctonus ponderosa. The transcription levels of these genes were different between larvae and adults of sexes, and there were significant differences among the different developmental stages, tissues, and between starvation and following re-feeding states. Additionally, injecting dsSK and dsSKR into beetles reduced the expression of the corresponding target gene, and increased their body weight. In parallel, injection of SK caused the increases of mortality and decreases of body weight, and also resulted in a decrease of glycogen and free fatty acid and an increase of trehalose. These results show that SK signaling plays a significant and positive role in the feeding regulation and provides a potential target for management of this pest.